METODE FUZZY TOPSIS MADM SEBAGAI ALTERNATIF PENGAMBILAN KEPUTUSAN MENENTUKAN PENERIMA BEASISWA PPA BERBASIS WEB - Halim, Bravura Candra; Alamsyah, Alamsyah; Sugiman, Sugiman (Universitas Negeri Semarang, 2016)
This study examines the decision making to determine the scholarship recipients Improving Academic Achievement (PPA) at the State University of Semarang (UNNES) with details of criteria that include student GPA, number of credits taken, the value of student affairs, and the income of parents. The decision making process admission PPA UNNES scholarship implemented with the programming language of PHP with MySQL database and calculations using the method of Fuzzy TOPSIS Multiple-Attribute Decision Making (MADM). The results of reception system PPA UNNES scholarship in this study is a ranking by 50 students of the value of the preferences of the applicants and then taken by students who ranked top 10 of the results of ranking of preferences for recommended escapes in scholarship acceptance PPA UNNES. Based on these results it can be concluded that a web-based decision support systems can be built using TOPSIS Fuzzy MADM with the structure of the programming language PHP and MySQL as a Database Management System (DBMS). In the development of future systems, can be done by adding other data supporting the selection of scholarship PPA